Accordion‐Like Motion in Electrochemically Switchable Crown Ether/Ammonium Oligorotaxanes. (6th February 2019) - Schröder, Hendrik V.; Stein, Felix; Wollschläger, Jan M.; Sobottka, Sebastian; Gaedke, Marius; Sarkar, Biprajit; Schalley, Christoph A.
Abstract: Reversible oxidation reactions in electrochemically switchable oligorotaxanes with tetrathiafulvalene (TTF) decorated 24‐crown‐8 ether wheels generate intramolecular mixed‐valence and radical‐cation interactions between the wheels. This induces shuttling of the wheels and a contraction of inter‐wheel distances. Further oxidation generates repulsive forces between the TTFs and maximizes the inter‐wheel distances instead. These interactions and co‐conformational changes were not observed for structurally similar controls in which acetyl groups along the axle prevent translational motion of the wheels. This operation mode of oligorotaxanes, which is reminiscent of an accordion‐like motion, is promising for functional materials and nanodevices such as piston‐type rotaxane motors. Abstract : Molekulares Akkordeonspiel : Das reversible Schalten von elektrochemisch steuerbaren Oligorotaxanen erzeugt eine akkordeonartige molekulare Bewegung. Elektrochemie, EPR‐ und UV/Vis‐NIR‐Studien zeigen, dass diese Art von Bewegung durch Gemischtvalenz‐, Radikalkation‐ und Coulomb‐Wechselwirkungen zwischen Tetrathiafulvalen‐dekorierten Kronenether‐Makrocyclen hervorgerufen wird.